Answer :

Let us assume x = a secθ


θ = sec–1 …(1)


we can write


Cot–1


= Cot–1


= Cot–1


= Cot–1


= Cot–1


= cot–1(cotθ )


= θ.


From 1 we get the given equation simplification to sec–1 .


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Prove the followiMathematics - Board Papers

Solve the followiMathematics - Board Papers